Pengaruh Media Pembelajaran Pop-Up Book Terhadap Hasil Belajar PKn Siswa Kelas V UPTD SD Negeri 122379 Pematang Siantar - Siahaan, Theresia Monika; Situngkir, Dian Agnes Carolin; Sihotang, Yulita Fitriani; Silitonga, Esra Melina; Hutasoit, Wenny Lasri; Purba, Nova Wanti; Sitohang, Edward Leonardo (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of using pop-up books as learning media on the Civic Education (PKn) learning outcomes of fifth-grade students at UPTD SD Negeri 122379 Pematang Siantar. The background of this study is the low PKn learning outcomes of students caused by conventional learning methods that do not actively involve students. This study uses a quantitative approach with a simple experimental method. The research subjects were one class, namely the fifth grade, consisting of 26 students. The research instrument was a written test consisting of a pretest and posttest to measure student learning outcomes before and after the application of pop-up books. The data obtained were analysed through instrument testing and statistical analysis to see the difference in learning outcomes. The results showed an increase in student learning outcomes after the use of pop-up books. Data analysis showed that pop-up book learning media had a significant effect on students' Civics learning outcomes. Thus, the use of pop-up book media proved to be effective in improving learning outcomes and could be used as an alternative learning media that was interesting and meaningful in Civics learning in primary schools.